Subnational Training on Use of the Kenya Meteorological Department’s ENACTS Maprooms: Western Kenya - Ruirie,Onesmus; Grossi, Amanda (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
Improved availability and quality of climate data and information has been necessary but not sufficient in the development of effective, decision-relevant, sustainable, and locally-led climate services for the agricultural sector in Kenya. In particular, while the Kenya Meteorological Department (KMD) has long produced high quality information available at high resolution, this has not been enough to ensure that it is easily accessed, understood, or able to be used at the sectoral level in decision nmaking for agriculture. Rather, intentional efforts to both promote the translation (contextualization) and transfer (communication) of this information alongside capacity building for its use have been needed.